2013
DOI: 10.1016/j.ncl.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Motor Neuropathy, Multifocal Acquired Demyelinating Sensory and Motor Neuropathy, and Other Chronic Acquired Demyelinating Polyneuropathy Variants

Abstract: Chronic acquired demyelinating neuropathies (CADP) are an important group of immune neuromuscular disorders affecting myelin. These are distinct from chronic inflammatory demyelinating polyneuropathy (CIDP). Classically, CIDP is characterized by proximal and distal weakness, large fiber sensory loss, elevated cerebrospinal fluid (CSF) protein content, demyelinating changes nerve conduction studies or nerve biopsy, and response to immunomodulating treatment. In this chapter we discuss CADP with emphasis on mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 151 publications
(154 reference statements)
1
35
0
8
Order By: Relevance
“…Anti‐MAG antibodies are positive in half to two‐thirds of DADS‐M neuropathy patients . DADS‐M neuropathy typically occurs in elderly men and is generally refractory to immunosuppressive therapy regardless of the anti‐MAG antibody status . DADS‐I neuropathy, similar to our patients, does not have the typical older age and male predominance of DADS‐M patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Anti‐MAG antibodies are positive in half to two‐thirds of DADS‐M neuropathy patients . DADS‐M neuropathy typically occurs in elderly men and is generally refractory to immunosuppressive therapy regardless of the anti‐MAG antibody status . DADS‐I neuropathy, similar to our patients, does not have the typical older age and male predominance of DADS‐M patients.…”
Section: Discussionsupporting
confidence: 57%
“…DADS‐I neuropathy, similar to our patients, does not have the typical older age and male predominance of DADS‐M patients. Response to immunomodulatory therapy of DADS‐I neuropathy is somewhere between DADS‐M and classical CIDP . It has been suggested that the response to immunotherapy in DADS‐I patients with pure sensory syndrome or sensory CIDP is difficult to measure, because there are only sensory manifestations .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, clinicians should not assume that their presence rules out a MADSAM diagnosis in favor of MMN. Similarly, the composite autoantibody profile between MMN and MADSAM patients may be in keeping with prior discussion of a potential overlap between the 2 conditions; however, the histopathologic findings of MADSAM are more in keeping with CIDP …”
Section: Discussionmentioning
confidence: 58%
“…Rarely, idiopathic pandysautonomic syndrome can be the only manifestation of a peripheral neuropathy without other motor or sensory findings. 25, 26 …”
Section: Important Information From the History And Physical - Six Kementioning
confidence: 99%